Optimization of intrauterine interventions in spontaneous abortion - I. A. Salov; I. V. Naumova; M. V. Lomovitskaya (Акушерство, гинекология и репродукция, 2024)
Introduction. Retained products of conception (RPOC) are detected in 15 % of women after spontaneous or medical abortion. RPOC blind removal from the uterine cavity remains the "gold standard" of surgical treatment, which, however, may be associated with a high risk of certain complications that pose a serious threat to female reproductive function and quality of life. An alternative method for eliminating RPOC proposed by operative hysteroscopy demonstrating the visual control advantages.Aim: to evaluate clinical effectiveness and safety of RPOC removal in incomplete spontaneous abortion using hysteroscopic morcellation.Materials and Methods. The prospective comparative study included 135 women with incomplete spontaneous abortion aged 18 to 40 years, divided into 3 groups: group 1 – 42 patients after RPOC electromechanical vacuum aspiration (EVA); group 2 – 44 patients after RPOC manual vacuum aspiration (MVA); group 3 – 49 patients after RPOC hysteroscopic morcellation (HM). In all patients, the level of total endotoxin was measured, metroaspirate cytokine profile was analyzed, the indicator of endometrial microcirculation was assessed before surgical treatment and on day 1 afterwards, and genital ultrasound examination was performed on day 3–5 post-surgery.Results. In the post-surgical vs. pre-treatment period, the EVA and MVA groups revealed significantly increased levels of total endotoxin and interleukin (IL) IL-1β (p < 0.05). In contrast, these parameters in the HM group changed insignificantly (p > 0.05). In all groups, IL-8 and tumor necrosis factor alpha (TNF-α) levels after surgery were significantly elevated (p = 0.001). In the EVA and MVA groups, levels of anti-inflammatory cytokines IL-4 and IL-10 were markedly decreased (p = 0.001), which did not change in the HM group (p > 0.05). A significantly accelerated microcirculation rate was noted in the EVA and MVA groups while comparing it at pre-surgery level (p = 0.001), but not in the HM group (p = 0.415). Incomplete RPOC removal was reported for 4.5 % MVA patients, all EVA and HM patients had total RPOC elimination. Intraoperative bleeding, uterine perforation were not reported in any examined patient.Conclusion. The early-stage treatment results showed that RPOC removal by the HM is an effective and safe approach. Limited inflammatory response and stable endometrial microcirculation upon using the HM evidence about a minimal impact on the endometrium that lowers probability of postoperative adhesion.